Theodicy as a social function and the age of secularization (Itinera, 2018)
This paper analyses both the possibility of interpreting theodicy as provided with a social function and that of a secularized version of the theodicy itself, characterised by a remarkable continuity between its religious version and the secularized one. To this purpose we focus on the functional analysis of theodicy, i. e. on the concrete effects that it has on society, and on its argumentative structure, reading it as a special kind of social justification; in particular, we underline the role of theodicy in the construction of meaning and its relations with ethics, the conception of justice and the presence of evil in the world. This interpretation is then tested by applying the theoretical conclusions thus obtained to a specific case: Weber’s analysis on Protestant ethic, since it exemplifies a theodicy with a clear social function. Lastly we apply this analysis to the historical case of Social Darwinism, interpreting it as a concrete instance of secularized theodicy; we especially focus on the thought and influence of Herbert Spencer and on its effects on his fervent, as well as probably most famous follower, Andrew Carnegie.